Gaps in climate health literacy: an analysis of Kosovo’s pre-university curricula and textbooks - Ramadani, Lira; Boeckmann, Melanie; Klüsener, Carolin; Sioen, Giles B. (Frontiers in Climate, 2025)
Climate change poses significant health risks, making education on mitigation and adaptation essential. Climate Health Literacy (CHL), recognized as vital in the global response to health impacts of climate change, is crucial for equipping individuals with the knowledge and skills needed to manage these challenges. However, CHL’s integration into school curricula remains largely unexplored. In Kosovo, climate change is expected to exacerbate existing environmental issues, yet awareness among young people is limited. This study investigates how climate and health topics are incorporated into Kosovo’s pre-university curricula and textbooks (ISCED levels 0–3), focusing on how these connections are addressed to promote CHL. In 2024, a content analysis was applied to Kosovo’s Core Curricula for Pre-Primary, Primary, Lower Secondary, and Upper Secondary Education (grades 0–12), issued in 2016, along with the Subject Syllabi for each grade, issued in 2018. Additionally, six textbooks identified through our curricula and syllabi review as covering climate and health topics were analyzed using a coding guide, which was developed specifically for this study based on previous research. The findings were then compared to an existing CHL framework to identify areas of alignment and gaps. The analysis found limited coverage focusing on climate and health across grade levels. In grades 0–5, only one curriculum topic related to climate change and health was identified, with no corresponding material in textbooks. Grades 6–9 included two topics, though these lacked exploration of the links between environmental pollution, climate change, and health. The highest integration was in grades 10–12, where four topics provided more in-depth discussion of these issues. Overall, Kosovo’s curricula and textbooks do not fully align with CHL recommendations. The limited coverage in early grades and the lack of interconnected content between climate change and health topics suggest areas for improvement. Increasing localized, context-specific content could enhance Climate and Health Literacy among students in Kosovo.